FORMATION OF COGNITIVE INDEPENDENCE FUTURE TEACHER IN THE STUDY PROCESS FOREIGN LANGUAGE AS A CURRENT PROBLEM MODERN PEDAGOGICAL SCIENCE (Pedagogy of Higher and Secondary Education, 2022)
The article deals with some actual problems concerning the formation o f future teacher cognitive self-directed activities in the process of foreign language studies.